Law in Action During Disaster Recovery in Lampung Coastal Village - Rudy, Rudy; Helvi Yanfika; Dorothy Rouly H. Pandjaitan; Martina Anggi Silova; Chaidir Ali (Indonesian State Law Review, 2025)
Post-disaster recovery serves as a crucial step within the broader framework of disaster management, acting to restore affected communities and environments to a state of resilience. However, the effectiveness of these recovery efforts is significantly undermined when they are not implemented in an integrative manner. This lack of cohesion can render the entire disaster management approach less impactful. This situation exemplifies the persistent challenges faced by disaster management models in Indonesia, particularly in the aftermath of significant events such as the 2018 tsunami that devastated the coastal regions of Lampung. This study employs socio-empirical research methods to analyze the post-disaster recovery model enacted by the National Disaster Management Agency (NDMA) across three coastal villages in Lampung. Through a comprehensive examination of the implemented strategies and their outcomes, the research team has identified critical shortcomings: specifically, the failure to adopt an integrative approach has led to inefficiencies and a lack of sustainability in the recovery efforts. As a response to these findings, this paper aims to establish a analytic of how law interact with the reality of disaster recovery through case studies on Tsunami Disaster Recovery by Government.